The Effect of Contralateral Head Rotation on Internal Jugular Vein to Carotid Artery Distance and Overlap Ratio - Heriwardito, Aldy; Dachlan, Muhammad Ruswan; Hidayat, Jefferson; Rokyama, Hadli (Bali Journal of Anesthesiology, 2019)
Introduction: Carotid artery puncture during central venous catheter (CVC) insertion could lead to serious complication if there was overlapping of internal jugular vein (IJV) and carotid artery (CA). IJV and CA overlap ratio and distance were determined by contralateral head rotation angle. Optimal angle of contralateral head rotation during CVC insertion can decrease the risk of CA puncture complication. This study was aimed to investigate the optimal angle of contralateral head rotation on IJV to CA distance and overlap ratio at the cricoid level by ultrasound guidance.Methods: This was a cross-sectional study of 34 patients undergoing elective surgery with CVC insertion. IJV to CA distance and overlap ratio at the cricoid level on each subject in supine position was measured by using two-dimensional ultrasound  (Sonosite® M-Turbo, 6-13 MHz probe) at 0o, 30o, 45o, 60o contralateral head rotation of insertion site. Collected data were analyzed using SPSS 21.0.Results: There were significant differences on IJV to CA distance and overlap ratio at different contralateral rotation angles (0o, 30o, 45o, 60o, p<0.001). Overlapping of IJV and CA started to occur at contralateral head rotation 30o (11.72%) and increased in line with the increasing of contralateral head rotation angle (21.21% at 45o).Conclusion: There were significant effects of contralateral head rotation to distance and overlapping IJV to CA at cricoid level. Optimal contralateral head rotation angle for CVC was less than 30o to prevent IJV and CA overlapping.